(untitled) (Research, Society and Development, 2022)
Myasthenia gravis (MG) is an autoimmune and chronic disease, characterized by interruption of neuromuscular communication, and its cause has not yet been fully elucidated. The objective of this study is to analyze how nursing helps in the process of improving the disease. This is an integrative literature review, carried out during the months of August and December 2022, in the SCIELO, LILACS, BRISA and MEDLINE databases, with the help of Health Sciences Descriptors (DeCS): Myasthenia Gravis; Congenital Myasthenic Syndrome of the Slow Canal and Motor Activity, the inclusion criteria were articles in Portuguese and English, published between 2018 and 2022 and free of charge, while the exclusion criteria were duplicate studies that were outside the topic. After sorting the articles, according to the inclusion and exclusion criteria, only 6 articles were selected to compose the final sample. It was concluded that the support of the nursing team in welcoming, encouraging, monitoring and assisting the patient, combined with drug therapy and the attention of the multidisciplinary team, provided a rapid improvement in the conditions of Myasthenia Graves.